Text’s transmission of Þe boke of ypocras: editing and studying its Early Modern English witness contained in London, Wellcome Library. MS 7117 (ff. 92r–94v) (ES Review. Spanish Journal of English Studies, 2025)
Þe boke of Ypocras is a zodiacal lunary which outlines the effects that the moon causes in each of the twelve zodiacal signs upon parts of the body leading to different diseases. During the Late Middle Ages this tract circulated extensively and was translated from Latin into different European vernaculars. Middle English manuscript witnesses have been recently studied (Diego Rodríguez, Þe boke). However, post-1500 witnesses remain unidentified and unedited. This paper aims to bring to light the sixteenth-century witness of Þe boke of Ypocras contained in London, Wellcome Library. MS 7117 (ff.92r–94). Its edition enables the identification of this witness and to place it in the line of transmission. Also, it provides new insights to reflect on how this treatise influenced the ongoing interpenetration of medical astrological thought in the sixteenth century
Keywords: Þe boke of Ypocras; Early Modern English manuscripts; astrological medicine; Wellcome Library MS 7117